Gravity and Telomeres - Aquilano, Roberto Oscar (2018)
Telomere shortening is a well-known process that is proposed to influence the pace of aging in every living being. On the other hand, telomere lengthening seems to be restricted to pluripotent cells and adult stem cell population, and it is mainly mediated by the enzyme telomerase. However, how is telomerase activation regulated in these compartments is largely unknown. Telomerase is also aberrantly upregulated in the vast majority of cancer cell where it allows for indefinite cell division. In previous papers, it has been put forth that time asymmetry is important to understand the cellular world, especially stem cells and cancer. This process could also be the cause of the telomerase activation and the corresponding telomere lengthening, but this stress mechanism described in the aforementioned articles could be extended to changes produced by the effects of gravity and the lack of gravity (weightlessness). This paper intends to expand on those previous papers.